Experimental Study on the Gas Flow Characteristics and Pressure Relief Gas Drainage Effect under Different Unloading Stress Paths. (12th August 2020) - Zhang, Chaolin; Xu, Jiang; Wang, Enyuan; Peng, Shoujian
Abstract : Coal seam gas is a critical substance because it can be a source of a large quantity of clean energy as well as a dangerous source of risk. A pressure relief gas drainage is an effective and widely used method for coal seam gas recovery and gas disaster control in coal mines. A series of pressure relief gas drainage experiments were conducted using large-scale coal samples under different unloading stress paths in this study to explore the unloading stress paths. From the experimental results, the dynamic evolutions of gas pressure, coal temperature, and gas production were analyzed. The trends of gas pressure and coal temperature during pressure relief gas drainage were similar: dropping rapidly first and then slowly with time. Correspondingly, gas production was fast in the early stage of pressure relief gas drainage and became stable thereafter. Meanwhile, gas flow characteristics were significantly affected by the unloading stress paths. Gas pressure and coal temperature had the maximum descent by unloading stress in three directions simultaneously, and the unloading stress of the Z direction had the minimal impact when only unloading in one direction of stress. However, the influence of unloading stress paths on gas production was complex and time dependent. The difference coefficient parameter was proposed to characterize the influence degree of unloading stress paths on the pressure relief gas drainage effect. Eventually, the selection of unloading stress path under different situations was discussed based on time, which is expected to provide the basis for pressure relief gas drainage.